Sugar palm (Arenga pinnata [Wurmb.] Merr) starch films containing sugar palm nanofibrillated cellulose as reinforcement: Water barrier properties. Issue 2 (3rd September 2019) - Ilyas, R. A.; Sapuan, S. M.; Atiqah, A.; Ibrahim, Rushdan; Abral, Hairul; Ishak, M. R.; Zainudin, E. S.; Nurazzi, N. M.; Atikah, M. S. N.; Ansari, M. N. M.; Asyraf, M. R. M.; Supian, A. B. M.; et al.
Abstract: Sugar palm fiber (SPF) is an agro‐waste plant that can be used as potential source of biomass for various biomaterial applications. In this study, sugar palm nanofibrillated cellulose (SPNFC) that was isolated from SPF was used as a nanofiller to reinforce sugar palm starch (SPS) to produce bionanocomposites. To attain SPNFCs, SPF was undergo strong acid and alkaline treatments. Later, the SPNFCs were prepared from SPFs via high pressurized homogenization process. The reinforcement of SPNFCs (0‐1.0 wt%) and SPS is done by using solution casting methods. The films were characterized in terms of physical properties such as light transmittance, moisture content, water solubility, and water absorption. The resulting nanocomposites permitted better water resistance, low moisture absorption, and low light transmittance as compared to control SPS film. Adding 1 wt% SPNFCs loading significantly improved the water absorption and water solubility of the composite film by 24.13% and 18.60%, respectively, compared with the control SPS film. This was attributed to the high compatibility between the SPNFCs and SPS matrixes, which composed of the multi‐hydroxyl polymer having three hydroxyl groups per monomer. Thus, this study is to show the potential of SPS/SPNFCs nanocomposite films in packaging industries.